PENGARUH DEBT TO EQUITY RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nurhaini Nurhaini; Leni Safitri (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
The purpose of this research is to test the influence of Earning Per Share and Debt to Equity Ratio to stock price on listed in Indonesia Stock Exchange. This study was conducted using secondary data. The sample technique used is purposive sampling. Of the ten companies, only five companies were selected, because they have complete financial report and earn positive profit respectively in 2010 - 2016. The analysis method used is multiple linear regression analysis. Based on the results of research show that partially Debt to Equity Ratio (DER) does not have a significant influence on stock prices, this is evidenced by t count t table (0.954 2.03452) and its significance greater than the probality value is 0.347 0.05. Partially Earning Per Share (EPS) has a significant influence on stock prices, this is evidenced by t count t table (8.386 2.03452) and its significance is smaller than its probability value of 0.000 0.05. And simultaneously Debt to Equity Ratio (DER) and Earning Per Share (EPS) have a significant effect simultaneously to stock price, this is evidenced by F count F table (40.147 4.14) and its significance is smaller than its probability value is equal to 0.000 0.05.